Correlates of maternal Emotional Stability: Findings from the Millennium Cohort Study. (1st October 2020) - Cheng, Helen; Furnham, Adrian
Abstract: This study explored correlates of maternal Emotional Stability drawing on a longitudinal data, from the Millennium Cohort Study (MCS): a sample of 10, 925 mothers. Data were collected when children were at ages 9 months, and then 3 and 7 years. Structural equation modelling showed that family poverty indicator, maternal psychological distress, parent-child relationship, and children's behavioural problems all had significant and direct effects on maternal trait Emotional Stability (Neuroticism), accounting for 26% of the total variance. The strongest predictor was maternal psychological distress, followed by children's behavioural problems. Further, maternal psychological distress had direct effects on both parent-child relationship and children's behavioural adjustment. The implications and limitations are discussed.